Schistosoma japonicum Cystatin Alleviates Sepsis Through Activating Regulatory Macrophages - Xie, Hong; Wu, Lingqin; Chen, Xingzhi; Gao, Shifang; Li, Huihui; Yuan, Yuan; Liang, Jinbao; Wang, Xiaoli; Wang, Shuying; Xu, Changyan; Chu, Liang; Zhan, Bin; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Multi-organ failure caused by the inflammatory cytokine storm induced by severe infection is the major cause of death for sepsis. Sj-Cys is a cysteine protease inhibitor secreted by Schistosoma japonicum with strong immunomodulatory functions on host immune system. Our previous studies have shown that treatment with Sj-Cys recombinant protein (rSj-Cys) attenuated inflammation caused by sepsis. However, the immunological mechanism underlying the immunomodulation of Sj-Cys for regulating inflammatory diseases is not yet known. In this study, we investigated the effect of Sj-Cys on the macrophage M2 polarization and subsequent therapeutic effect on sepsis. The rSj-Cys was expressed in yeast Pichia pastoris. Incubation of mouse bone marrow-derived macrophages (BMDMs) with yeast-expressed rSj-Cys significantly activated the polarization of macrophages to M2 subtype characterized by the expression of F4/80+ CD206+ with the elated secretion of IL-10 and TGF-β. Adoptive transfer of rSj-Cys treated BMDMs to mice with sepsis induced by cecal ligation and puncture (CLP) significantly improved their survival rates and the systemic clinical manifestations of sepsis compared with mice receiving non-treated normal BMDMs. The therapeutic effect of Sj-Cys-induced M2 macrophages on sepsis was also reflected by the reduced pathological damages in organs of heart, lung, liver and kidney and reduced serological levels of tissue damage-related ALT, AST, BUN and Cr, associated with downregulated pro-inflammatory cytokines (IFN-gamma and IL-6) and upregulated regulatory anti-inflammatory cytokines (IL-10 and TGF-β). Our results demonstrated that Sj-Cys is a strong immunomodulatory protein with anti-inflammatory features through activating M2 macrophage polarization. The findings of this study suggested that Sj-Cys itself or Sj-Cys-induced M2 macrophages could be used as therapeutic agents in the treatment of sepsis or other inflammatory diseases.